R&D, scale effects and spillovers: New insights from emerging countries - Kul Bahadur Luintel; Mosahid Khan (Cardiff University, Cardiff Business School, 2016)
There has been a concomitant rise in R&D and the rate of economic growth in emerging countries. Analyzing a panel of 31 emerging countries, we find convincing evidence of scale effects which make government policies potent for long-run growth. This contrasts sharply with the well known findings of Jones (1995a). Innovations show increasing returns to knowledge stock, implying that the diminishing returns assumed by some semi-endogenous growth models might not be generalized. International R&D spillovers raise the innovation bar. The observed growth rates of emerging economies appear in transition therefore their growth rates may recede with the passage of time.
Keywords: O3; O4; O47; 330; Scale Effects; Ideas Production; Diffusion; Panel Integration and Cointegration